An Analysis of Students’ Ability in Using Degrees of Comparison in Adjective and Adverb at English Language Education Program of UNP - Nur Azmi Novzalia; Senorica Yulia Sari (Journal of English Language Teaching, 2022)
The purpose of this study was to analyze the ability of fifth-semester students in the English Language Education Program UNP's use degrees of comparison in adjectives and adverbs. The Participants in this study were 35 fifth-semester students at the English Language Education Program of the UNP. This study was a quantitative study. Tests and interviews were conducted for this study. According to the study's findings, 55.42% of students were able to master the items of positive degrees in adjectives, followed by the items of comparative degrees in adjectives, with 61.14% of students being able to master those items. Of the students, 77.14% demonstrated the ability to master the items of the superlative degree in adjectives. In terms of adverbs, 72.57% of students were able to master the items of positive degree in adverbs, 66.85% of students were able to master the items of comparative degree in adverbs, and 38.28% of students were able to master the items of superlative degree in adverbs. This indicates that more than 50% of the students had mastered the degree of comparison. The respondents supported this finding, stating that the fifth-semester students in the English language education program have problem comprehending comparisons for the following reasons: They misplaced the article “the” in the superlative form and forgot to add “than” after the adjective in the comparative form. They also did not know how to modify words that ended in -y to -i and add -er/-est. Finally, they did not understand the purpose of using irregular forms.